Thermodynamic studies on removal reactive orange 16 dye on cross-linked chitosan/oil palm ash composite beads - Masitah, Hassan; Bassim, H. Hameed, Prof. Dr.; A. L., Ahmad (Universiti Malaysia Terengganu (UMT), 2011)
Environmental Science and Technology Conference 2009 (ESTEC 2009), organized by Universiti Malaysia Terengganu, from 7th - 8th December 2009 at Kuala Terengganu, Terengganu, Malaysia.